Reading Words or Pictures: Eye Movement Patterns in Adults and Children Differ by Age Group and Receptive Language Ability - An, Licong; Wang, Yifang; Sun, Yadong (Frontiers in Psychology, 2017)
Abstract: This study was conducted to explore the differences in the degree of attention given to Chinese print and pictures by children and adults when they read picture books with and without Chinese words. We used an eye tracker from SensoMotoric Instruments (SMI) to record the visual fixations of the subjects. The results showed that the adults paid more attention to Chinese print and looked at the print sooner than the children did. The stronger the children’s receptive language abilities were, the less time it took them to view the pictures. All participants spent the same amount of time looking at the pictures whether Chinese words were present or absent.